Strategy for Developing Sustainable Dryland Farming Systems in the Buffer Zone of the Mandalika Special Economic Zone, Indonesia - Candra Ayu; Sukardi; Tajidan; Hayati (Jurnal Penelitian Pendidikan IPA, 2026)
The Mandalika Special Economic Zone (KEK) buffer zone in West Nusa Tenggara Province, Indonesia, has a dryland farming system that supports tourism activities. This study aims to examine the existing conditions of the role of dryland farming systems in the area around the Mandalika SEZ as a buffer zone and develop strategies for developing dryland farming systems in the buffer zone to ensure sustainability. The analytical tools used in the study include descriptive analysis, SWOT analysis, and AHP analysis. The results show that the existing conditions of the Mandalika SEZ buffer zone related to sustainable dryland farming systems play a significant social and economic role. Meanwhile, the AHP results prioritize the SWOT groups as follows: strengths (54.3%), opportunities (26.2%), weaknesses (12.7%), and threats (6.8%); with the most important factor being farmer resilience in dryland farming. The recommended Grand Strategy is to optimize farmer potential through agricultural land expansion, diversification, and mixed farming, support from Village Cooperatives, and increasing the role of agricultural extension.